2022
DOI: 10.9734/cjast/2022/v41i464023
|View full text |Cite
|
Sign up to set email alerts
|

Slip Effect on Magnetohydrodynamic Boundary Layer Flow of Nanofluid over an Stretching Sheet with Thermal Radiation and Thermal Convective Boundary Condition

Abstract: The objective of the current analysis is to study the influence of MHD on flow of an ethylene glycol-based nanofluid containing copper nanoparticles through a exponential stretching sheet. Several parameters including Dufour, thermal radiation, Magnetohydrodynamic (MHD), and Eckart number, were investigated for their impacts on fluid flow, heat and mass transfer profiles, and thermal convective boundary conditions, while Navier velocity slip was also considered. The basic PDEs are transformed into nondimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Power production, medicinal uses such as magnetic medication targeting and blood flow metering, microfluidic pumps, and treatment of cancer employing magnetic nanoparticles are just a few of its applications. MHD is helpful in a wide range of sectors because it enables exact control and manipulation of fluids and particles [26][27][28][29][30]. Ishak et al [31] concluded that transverse magnetic fields have the effect of suppressing the velocity profiles that in response cause an enhancement in the temperature profiles.…”
mentioning
confidence: 99%
“…Power production, medicinal uses such as magnetic medication targeting and blood flow metering, microfluidic pumps, and treatment of cancer employing magnetic nanoparticles are just a few of its applications. MHD is helpful in a wide range of sectors because it enables exact control and manipulation of fluids and particles [26][27][28][29][30]. Ishak et al [31] concluded that transverse magnetic fields have the effect of suppressing the velocity profiles that in response cause an enhancement in the temperature profiles.…”
mentioning
confidence: 99%